Genomic analyses of Staphylococcus aureus clonal complex 45 isolates does not distinguish nasal carriage from bacteraemia. Issue 8 (15th August 2020) - Roe, Chandler; Stegger, Marc; Lilje, Berit; Johannesen, Thor Bech; Ng, Kim Lee; Sieber, Raphael N.; Driebe, Elizabeth; Engelthaler, David M.; Andersen, Paal Skytt
Abstract : Staphylococcus aureus is a colonizing opportunistic pathogen and a leading cause of bloodstream infection with high morbidity and mortality. S. aureus carriage frequency is reportedly between 20 and 40 % among healthy adults, with S. aureus colonization considered to be a risk factor for S. aureus bacteraemia. It is unknown whether a genetic component of the bacterium is associated with S. aureus bacteraemia in comparison to nasal carriage strains. Previous association studies primarily focusing on the clinical outcome of an S. aureus infection have produced conflicting results, often limited by study design challenged by sample collections and the clonal diversity of S. aureus . To date, no study has investigated whether genomic features separate nasal carriage isolates from S. aureus bacteraemia isolates within a single clonal lineage. Here we have investigated whether genomic features, including single-nucleotide polymorphisms (SNPs), genes, or kmers, distinguish S. aureus nasal carriage isolates from bacteraemia isolates that all belong to the same clonal lineage [clonal complex 45 (CC45)] using whole-genome sequencing (WGS) and a genome-wide association (GWA) approach. From CC45, 100 isolates (50 bacteraemia and 50 nasal carriage, geographically and temporally matched) from Denmark were whole-genome sequenced and subjected to GWA analyses involving gene copy number variation, SNPs, gene content, kmers and gene combinations, while correcting for lineage effects. No statistically significant association involving SNPs, specific genes, gene variants, gene copy number variation, or a combination of genes was identified that could distinguish bacteraemia isolates from nasal carriage isolates. The presented results suggest that all S. aureus nasal CC45 isolates carry the potential to cause invasive disease, as no core or accessory genome content or variations were statistically associated with invasiveness.